Implementation of Building Construction Management - Anwar, Rizali Roy; Pratikso, P; Wibowo, Kartono; Sulistyo, Juny Andry (JACEE (Journal of Advanced Civil and Environmental Engineering), 2025)
The problem of building construction on soft soil of the structure, so that at the planning stage it is known that there are quite a lot of design criteria, especially in the lower building structure and ground floor. Similarly, during the development phase, construction equipment and methods face the problem of a very high level of risk analyst on soft soil conditions and prone to subsidence. Resource risk plays an important role in the project time frame on infrastructure projects on soft soils during the construction phase. The use of Decision Support System (DSS) for construction project management with a Scientific Evolution Analysis approach., The methodology used is that building repair priorities can be used using the Analytical Hierarchy Process (AHP) and Profile Matching methods. The method is carried out by the implementation of building construction, which is analyzed using the Analytical Hierarchy Process (AHP) method with Excel application software. The decision-making system model was created by generating a computer-based Building Information Management (BIM) application with MySQL. The results of this study are several alternative construction design designs for the bottom of buildings on soft soil depending on the number of floors that greatly affect the type of underground building other than the type of soil, or without D walls and piles and the model developed makes it easy to choose the type of foundation because it is computer-based with PHP-MySQL program.